REPRESENTASI CANTIK IKLAN WARDAH DI TELEVISI: Studi Analisis Semiotik Iklan Wardah Exclusive Series Versi Dewi Sandra In Paris - Anisa Rohmah Sahara; Irma Rumtianing Uswatul Hanifah (Dialogia, 2019)
Abstract: As a product that uses the label "halal" and often incorporates religious elements such as the Muslim model, for the market share of Muslim women who are the majority religion in Indonesia. Many product advertisers want to convey a message to their viewers to be the center of attention, including Wardah's cosmetics ads. Wardah's cosmetics ad tries to convey a message to viewers about beauty through the Wardah Exclusive Series version of Dewi Sandra In Paris. This study also aims to obtain information about beautiful representations in the Wardah Exclusive Series version of Dewi Sandra In Paris advertisements found on television. This research is a qualitative research with a paradigm of criticism to reveal the beautiful representation that an advertisement wants to convey. Data collection techniques are done using document analysis. Meanwhile, the data analysis technique is the analysis of Charles Sanders Peirce's semiotics. Charles's theory divides signs based on icons, indexes, and symbols.الخلاصة:  فمن المعروف، استخدم نتاج الوردة تسميات "الحلال" في سائر منتوجاته. ومن ثمّ أدخل عناصر الدّين بصورة استخدام الفنّانة المسلمة لارتفاع المزاد في بلاد إندونيسيا، نظرا إلى أنّ أغلابيّة المواطنين فيه مسلم. وأما الرسالة من اظهار الإعلان هي أن يكون البضائع في الإعلان محور الاهتمام، وثمّة الهدف من اعلان الوردة. وحاولت الوردة الإشارة إلى جمال المرأة من خلال تقديم الاعلان لنتاج الوردة الحصرية المعترضة (Exclusive Series) بصيغة دوي سندرا فى بلاد باريس.  وبجانب ذلك، أنّ الأهداف من كتابة هذه المقالة هي الوصول إلى بيانات المميزة عن تمثيل الجمال عند إعلان الوردة الحصرية المعترضة بصيغة دوي سندرا ببلاد باريس في التلفزيين. واستخدمت هذه المقالة منهج البحث الكيفي بنماذج النّقد، والأهداف منه للكشف عن تمثيل الجمال عند إعلان الوردة.  وأما الطريقة المستخدمة لجمع البيانات هي بتحليل الوثائق. وأما طريقة تحليل البيانات المستخدمة هي طريقة تحليل السيميائية عند جرليس سندير فيريج بنظرية جرليس (Charles Sanders Peirce) لتقسيم العلامة حسب  الرموز المؤشّر وما أشبه ذلك.   Abstrak: Sebagai produk yang menggunakan label “halal” dan kerap memasukkan unsur keagamaan seperti model muslimah, untuk pangsa pasar muslimah yang menjadi agama mayoritas di Indonesia. Banyak pengiklan produk yang ingin menyampaikan pesan kepada pemirsanya supaya menjadi pusat perhatian, tak terkecuali iklan kosmetik Wardah. Iklan kosmetik Wardah mencoba menyampaikan pesan terhadap pemirsa mengenai cantik melalui iklan Wardah Exclusive Series Versi Dewi Sandra In Paris. Penelitian ini juga bertujuan untuk memperoleh informasi tentang representasi cantik dalam iklan Wardah Exclusive Series Versi Dewi Sandra In Paris yang terdapat di televisi. Penelitian ini merupakan penelitian kualitatif dengan paradigma kritik untuk mengungkap representasi cantik yang ingin disampaikan sebuah iklan. Teknik pengumpulan data dilakukan dengan menggunakan analisis dokumen. Sedangkan, teknik analisis data adalah analisis semiotika Charles Sanders Peirce. Teori Charles membagi tanda berdasarkan ikon, indeks, dan simbol.